The Palliative Function of Hostile Sexism among High and Low-Status Chilean Students - Vargas-Salfate, Salvador (Frontiers in Psychology, 2017)
Previous studies have demonstrated that justifying the social, economic, and political systems is associated with psychological well-being, which has been termed as the palliative function of ideology. However little research has been conducted on gender stereotypes among children, comparing by socioeconomic status. This study aimed to fill this gap in the system justification literature. We present data from the Chilean version of the International Survey of Children Well-Being (ISCWeB), which was conducted in 2012. We found that the palliative function of gender stereotypes is present among this sample, being qualified by a socioeconomic status by hostile gender stereotype interaction. In other words, the effect on the psychological well-being was observed in low-status, but not in high-status students. These results extend the previous knowledge about the palliative function of the ideology, suggesting why the low-status members of a society actively engage in system justification.